TandemTrack: Shaping Consistent Exercise Experience by Complementing a Mobile App with a Smart Speaker - Luo, Yuhan; Lee, Bongshin; Choe, Eun Kyoung (Proceedings of the ACM Conference on Human Factors in Computing Systems, 2020)
Smart speakers such as Amazon Echo present promising opportunities for exploring voice interaction in the domain of inhome exercise tracking. In this work, we examine if and how voice interaction complements and augments a mobile app in promoting consistent exercise. We designed and developed TandemTrack, which combines a mobile app and an Alexa skill to support exercise regimen, data capture, feedback, and reminder. We then conducted a four-week between-subjects study deploying TandemTrack to 22 participants who were instructed to follow a short daily exercise regimen: one group used only the mobile app and the other group used both the app and the skill. We collected rich data on individuals’ exercise adherence and performance, and their use of voice and visual interactions, while examining how TandemTrack as a whole influenced their exercise experience. Reflecting on these data, we discuss the benefits and challenges of incorporating voice interaction to assist daily exercise, and implications for designing effective multimodal systems to support self-tracking and promote consistent exercise.